MODIFIKASI MEDIA TANAM UNTUK MENINGKATKAN MUTU BIBIT HANDEULEUM (Graptophyllum pictum L. (Griff.)) DARI BEBERAPA MACAM ASAL STEK : - - Rahayu, Tri; Ihsan, Mohamad; Pamujiasih, Tri (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2021)
The research titled "Modification of Planting Media to Improve the Quality of Handeuleum (Graptophyllum Pictum L.) Seedling from Several Kinds of Cuttings Source", was conducted in Sukoharjo, Central of Java. The first treatment was the kind of cuttings source, namely: cuttings from the shoot (S1), cuttings from the second section (S2), and cuttings from the third section (S3). The second treatment factor is the kind of media: sandy soil media (M1), rockwool media (M2), and cocopeat media (M3). The data obtained were analyzed by using the F test at 5% and 1% significantly levels, while the follow-up test was carried out using Duncan's multiple range test at the 5% significantly level. The results obtained indicated that the S treatment (kind of cuttings source) had a significant effect on the variables of the number of branches, number of leaves, and leaf area of ​​each seedling. The highest number of branches and leaves was achieved in the S3 treatment (third section cuttings), followed by S2 (second section cuttings) and S1 (shoot cuttings) treatments. There were a significant difference between the treatments. In leaf area variables, the highest yield was achieved at S1 (shoot cuttings), followed by S2 and S3 which were significantly different between each other. Treatment S showed no significant effect on variables the appearance time of the buds, fresh weight of leaves and dry weight of leaves. The treatment of various media had a significant effect on the leaf area variables of each seedling. Cocopeat media (M3) produced the highest leaf area, followed by M1 (sand media), and M2 (rockwool media) treatments. There was no interaction between treatments of kind of cuttings source and types of media for all observed variables.